Kondisi Kesehatan Karang Genus Porites di Perairan Jemeluk dan Penuktukan-Bali - Ni Luh Putu Febbi Mellani; I Gede Hendrawan; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2019)
This research was conducted to determine the coral health condition of genus Porites at Jemeluk beach and Penuktukan beach with the different of reef geomorphology. Coral reef data was collected for two days in Jemeluk beach (reef flats) in March 2017 and in Penuktukan beach (reef slope) in April 2017. Each observation location consisted of 3 stations parallel to the coastline. Observation of coral health data using belt transect method size 2 x 25 m with width of 1 meter each to left and right side. Photo documentation was performed on coral reefs of Porites and subsequently identified the types of diseases and forms of health problems using Coral Disease Handbook, Guidelines for Assessment, Monitoring and Management. The types of coral diseases found in both beaches are ulcerative white spot and white plague. The number of dominant colonies that infected with the disease was found on Jemeluk beach which has coastal morphology of coral reefs. The coral health conditions of the genus Porites found on Jemeluk and Penuktukan beaches are in an unhealthy condition. Compromised health is dominant in Jemeluk beach, this is estimated to be caused by the presence of river flow at observation sites which is relatively high. In addition, the coral reef morphology in Jemeluk beach is reef flat causing the reefs in this area to be more susceptible to damage.